1995
DOI: 10.1159/000236946
|View full text |Cite
|
Sign up to set email alerts
|

Substance-P-lnduced Histamine Release from Human Nasal Mucosa in vitro

Abstract: There is growing evidence that substance P (SP) is one of the main neuropeptides involved in neurogenic inflammation of the airways. However, a number of studies were not able to demonstrate histamine release from human mucosal mast cells after SP administration. Since cultures of isolated cell systems provide only a partial picture of the inflammatory processes in vivo, organ culture models promise to offer physiologically relevant assay systems for studying tissue interactions. Thus, we examined the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Unfortunately, very little work on specifically human nasal mucosa has been reported. Previously, we described a culture system of human nasal mucosa (12,13) on gelatin sponges at the air-liquid interface.…”
mentioning
confidence: 99%
“…Unfortunately, very little work on specifically human nasal mucosa has been reported. Previously, we described a culture system of human nasal mucosa (12,13) on gelatin sponges at the air-liquid interface.…”
mentioning
confidence: 99%
“…Schierhorn et al [16] reported that SP induced histamine release from mast cells into the human nasal mucosa. In addition, the effects of neurotransmitters were greatly influenced by their splitting enzyme [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is anatomical support for this contention since sensory nerves have been found near mast cells in various tissues including the airways [45]. SP, or stable analogs thereof, have been shown to elicit histamine release from guinea pig lungs in vivo [46] and human pulmonary mast cells [47] and nasal mucosa in vitro [48]. In our own studies SP-induced plasma protein extravasation in guinea pig airways was apparently not mediated by histamine (which may have been released from mast cells in response to the neuropeptide) since a maximally effective dose of pyrilamine did not modify the effect.…”
Section: Discussionmentioning
confidence: 99%